Adrenal Myelolipoma - Khadka, B; Karki, D B; Parmer, B (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
Adrenal myelolipoma is a rare, benign, usually unilateral, endocrinologically inactive tumor composed of mainly mature adipose tissue and hematopoietic elements that resemble bone marrow. It almost always occurs within adrenal gland but they have been reported in other locations. Most patients are asymptomatic and the lesion is discovered incidentally. We report a case of 35 years old lady who had just come for regular check up with vague abdominal discomfort on right side. Radiological investigations showed a large right sided adrenal myelolipoma. Image guided fine needle aspiration cytology was done, which confirmed the diagnosis. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.12002 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 Page: 50-51